Economic evaluation of management strategies for complex regional pain syndrome (CRPS) - Zhou, Xiaofeng; Zhou, Yi; Zhang, Xiaofei; Jiang, Feng (Frontiers in Pharmacology, 2024)
The economic impact of Complex Regional Pain Syndrome (CRPS) on both patients and the global healthcare system continues to escalate. However, the economic implications associated with management interventions for CRPS have received limited attention. Therefore, our objective is to perform a thorough examination of published economic assessments of the various management strategies utilized for CRPS.Methods: A thorough search spanning four general medical databases and three health economic databases to identify full economic evaluations on CRPS management stages from January 1994 to June 2023 were conducted.The quality of these studies were evaluated by employing the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) statement. To enable cross-study comparisons conducted in different countries, we adjusted the costs reported in the selected studies for inflation and converted them into 2023 US dollars.Results: A total of nine economic evaluations, consisting of eight high-quality and one medium-quality, were identified across five nations during a span of 29 years. The findings suggest that the most economically efficient intervention for CRPS are interventional approaches of Spinal Cord Stimulation (SCS) in comparison to conventional management for long periods of time. Furthermore, in situations where there is a limited time period of less than one year, rehabilitation therapies, particularly physical therapy, have been demonstrated to be more effective in terms of both cost and clinical outcomes.The interventional management strategies, particularly for severe and persistent CRPS over long periods, may offer the greatest cost efficiency. In conditions with limited timelines, rehabilitation measures, such as rehabilitation therapies, can be cost-effective. However, insufficient data for other common interventions prevents the formation of a definitive conclusion. Similarly, it is crucial to recognize that the results of these interventions might be affected by the selection of comparator and the threshold for willingness to pay.